Pemphigus Foliaceus in an 11-Year-Old Mexican Girl with Response to Oral Dapsone. (12th December 2013) - García-Meléndez, Martha Elena; Eichelmann, Kristian; Salas-Alanís, Julio César; Gomez-Flores, Minerva; Ocampo-Candiani, Jorge
Abstract : Pemphigus foliaceus (PF) is rarely described in the pediatric population with less than 40 cases reported in the literature. We report the case of an 11-year-old girl who was diagnosed with PF after 6 months of starting with symptoms and who responded well to therapy with oral dapsone. Although therapeutic guidelines for PF in children are lacking, oral corticosteroids in combination with dapsone have proven to be effective as first-line treatment in this setting.